An investigation into the aspirations, governance and management challenges of Māori farming trusts. (December 2016) - Phillips, Tom; Woods, Christine; Lythberg, Billie
This article investigates areas for possible improvement in the governance and management of large New Zealand Māori dairy farm businesses. Building on the innovative practices of their tūpuna (ancestors), Māori are defining their own aspirations, realities and goals in the dairy farming world and their accompanying challenges, as expressed by individuals and collectives currently engaged in Māori dairy farm businesses. The Māori way of doing business is described in this study as having a 'quadruple bottom line' of profit, people, environment and community business objectives. Māori are genuine leaders of dairy farm environmental management, due in part to their attitudes to land ownership, business values and holistic world views. The top tier of Māori farming trusts comprises fast growing enterprises, which are rapidly improving business performance. The expertise and governance of large corporate farms have much to offer other farming businesses.